European Integration: Some stylised facts - Finn Olesen; Jørgen Drud Hansen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2000)
The European economic integration has been an ongoing process for nearly a half century. This article discuss initially the concept of integration and then gives an overall assessment of the development of integration on various areas. Evidence points to a remarkable process towards monetary integration especially in the last decades. The significant increase of the intra-EU trade also points to a more integrated Europe especially since the establishing of the internal market. However, the integration seems to have less impact on other areas e.g. synchronisation of the business cycles between Member States and convergence of living standards. Prospects for the future development of integration is also discussed in the article.
Keywords: 330; Europäische Integration